Synergistic effects of warming and disease linked to high mortality in cool-adapted terrestrial frogs. (May 2020) - Neely, Wesley J.; Greenspan, Sasha E.; Ribeiro, Luisa P.; Carvalho, Tamilie; Martins, Renato A.; Rodriguez, David; Rohr, Jason R.; Haddad, Célio F.B.; Toledo, Luís Felipe; Becker, C. Guilherme
Abstract: Cool-adapted species inhabiting montane tropical forests are vulnerable to heat stress associated with climate warming. According to the thermal mismatch hypothesis, pathogens are predicted to have broader thermal tolerances than their hosts, which can lead to increased pathogen loads and host mortality when temperatures are outside hosts' thermal optima. We tested the thermal mismatch hypothesis in two habitat generalist species expected to have wide thermal tolerance ranges: Dendropsophus minutus captured at a high elevation and D . elegans captured at a warmer low elevation. We also tested high-elevation individuals of the Brazilian direct-developing species Ischnocnema parva, which are expected to have a narrow thermal tolerance range based on life history. We exposed all frogs to the pathogenic fungus Batrachochytrium dendrobatidis ( Bd ) under three temperatures ranging from the average nighttime temperature where frogs were collected (16 and 21 °C for high and low elevations, respectively) to a simulated warming event (26 °C). Bd loads across all three host species were negatively associated with temperature. However, the interaction between Bd infection and warming led to increased mortality in cool-adapted I. parva at higher temperatures, despite lower infection loads. Our results indicate that Bd may lead to declines of cool-adapted montane frogs under the combined pressures of pathogen infection and warming, even at temperatures approaching the pathogen's upper thermal limit. Thus, climatic warming at a level that lowers fitness of heat-sensitive pathogens may not uniformly reduce host disease risk.